Isolation and characterization of a novel goose ovaritis-associated cluster 3 Tembusu virus - Jing-Ying Liao; Hui Tang; Wei-Jie Xiong; Tian-Ning Liu; Jie-Yu Li; Jun-Yong Xia; Chao-Ting Xiao (Poultry Science, 2023)
ABSTRACT: Tembusu virus (TMUV) is a member of the genus Flavivirus in the family Flaviviridae. Currently, TMUV was classified into 4 distinct clusters, with cluster 2 strains widely distributed in duck and goose populations in Asia, causing significant economic losses to the producing industries. In this study, a novel TMUV strain TMUV/goose/CHN/2019/HNU-NX2 (HNU-NX2-2019) was isolated and characterized from geese with ovaritis from Hunan province, China. Phylogenetic analyses of genome and the E gene indicated the present TMUV could be grouped into the newly defined TMUV cluster 3. The genome of HNU-NX2-2019 showed the highest identities of 98.1% to 98.2% to the cluster 3 TMUVs newly identified in 2020 and 2021 from chickens with a severe egg-drop syndrome from Guangdong, Guangxi and Shandong provinces of China, which were all showing a close relation to a mosquito-origin TMUV (KT607936) identified in 2012. Further experiments confirmed HNU-NX2-2019 could grow well in chicken fibroblast cell line DF-1 and in SPF chicken embryos, with titers varied from 107.3 to 108.8 viral genomic copies per mL in the culture solutions. A pilot virus challenge study in 3-day-old chicks demonstrated that this virus could efficiently infect chicks with virus distributed in the brains, small intestines and other visceral organs, with titers varied from 105.4 to 106.7viral genomic copies per gram of the tissues. Furthermore, HNU-NX2-2019 can induce specific antibody in ducklings but with no obvious disease and virus shedding, and on necropsy no TMUV was detected in the tissues in the present study. This is the first report to identify a novel cluster 3 TUMV from goose, and further demonstrated this goose TMUV strain could infect chicken efficiently but not in ducklings under the present experimental conditions, which highlighted intensive attentions may be paid to this novel mosquito-origin cluster 3 TMUV.